Modern Kazakh art and institutions - Gaini S. Mukhtarova, Ardak K. Yussupova, Gulzada A. Khussainova, (Opción, 2019)
This article analyzes how the infrastructure of modern fine and music arts are being formed and developed in the Republic of Kazakhstan via theoretical and empirical methods such as comparative analysis of sources on the research problem. As a result, the Union of Artists helped them to own creative workshops, receive State orders, craft materials and paints, etc. As a conclusion, there is a need in art ecology, in observing legal, moral, even ethical norms, well-thought-out regulatory measures, developing quality policy in the field of culture and art at all levels, including the State level.